Building knowledge economies in Africa: An introduction - Simplice Asongu; John E. Kuada (African Governance and Development Institute (AGDI), 2020)
Knowledge has emerged as a fundamental driver of economic growth and development by inter alia improving the effectiveness and efficiency of economic projects and boosting the process of finding new avenues of addressing developmental policy syndromes. Recent evidence suggests that Africa is on the threshold of significant and sustainable economic growth if its human and material resources can be effectively mobilised to support the process (Kuada & Mensah, 2017; Asongu & Tchamyou, 2019). Consequently, the World Bank's Knowledge Economy Framework aims to explore and support the extent to which current policies in African countries affect the knowledge development process (and thereby competitiveness) on the continent. A knowledge economy is an economy in which economic prosperity largely depends on the accessibility, quality and quantity of information available, instead of the means of production (Asongu, 2017a, 2017b). This themed issue of Contemporary Social Science-'Building Knowledge Economies in Africa' - consists of papers that focus on, but are not limited to, the four dimensions of the World Bank's Knowledge Economy Index. These are: information and communication technology, education, economic incentives and institutional regime, and innovation (Tchamyou, 2017). The themed issue engages with high quality contributions which, taken together, address the drivers towards knowledge-based economies. This introduction provides a context for understanding the importance of building knowledge economies in Africa and summarises the main contributions to the themed issue. The paper ends by advising scholars and policy makers regarding the risks associated with a colonial view of knowledge- notably the importance of proposing knowledge-based policies while avoiding hegemonic paradigms and hierarchical constructs. In summary, the issue consists of a set of theoretically informed, empirically robust, policy-relevant and accessible articles for both specialists and non-specialists.
Keywords: O10; O30; O38; O55; O57; 330; Knowledge economy; Development; Africa